2014
DOI: 10.1126/science.1242353
|View full text |Cite
|
Sign up to set email alerts
|

Fermi-LAT Observations of the Gamma-Ray Burst GRB 130427A

Abstract: The observations of the exceptionally bright gamma-ray burst (GRB) 130427A by the Large Area Telescope aboard the Fermi Gamma-ray Space Telescope provide constraints on the nature of these unique astrophysical sources. GRB 130427A had the largest fluence, highest-energy photon (95 GeV), longest γ-ray duration (20 hours), and one of the largest isotropic energy releases ever observed from a GRB. Temporal and spectral analyses of GRB 130427A challenge the widely accepted model that the nonthermal high-energy emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
240
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 282 publications
(269 citation statements)
references
References 39 publications
(24 reference statements)
19
240
1
1
Order By: Relevance
“…GRB 120711A and GRB 130427A (e.g. Laskar et al 2013;Perley et al 2014;Preece et al 2014;Vestrand et al 2014;Ackermann et al 2014) are two powerful bursts with E γ,iso ∼ 10 54 erg in the 1 keV−10 MeV energy range (about one order of magnitude higher than that estimated for GRB 041219A (McBreen et al 2006;Götz et al 2011)) and long-lived soft γ-ray afterglow emission (∼10 ks for GRB 120711A and ∼1 ks for GRB 130427A). The soft γ-ray detection from GRB 130427A is most likely limited by the Swift/BAT sensitivity considering that the LAT emission was detectable for longer than a day.…”
Section: Grb 120711a As a Member Of The Long Grb Populationmentioning
confidence: 99%
“…GRB 120711A and GRB 130427A (e.g. Laskar et al 2013;Perley et al 2014;Preece et al 2014;Vestrand et al 2014;Ackermann et al 2014) are two powerful bursts with E γ,iso ∼ 10 54 erg in the 1 keV−10 MeV energy range (about one order of magnitude higher than that estimated for GRB 041219A (McBreen et al 2006;Götz et al 2011)) and long-lived soft γ-ray afterglow emission (∼10 ks for GRB 120711A and ∼1 ks for GRB 130427A). The soft γ-ray detection from GRB 130427A is most likely limited by the Swift/BAT sensitivity considering that the LAT emission was detectable for longer than a day.…”
Section: Grb 120711a As a Member Of The Long Grb Populationmentioning
confidence: 99%
“…When sufficient photon statistics were available, their GeV emission was also found to be harder than the extrapolation of their keV−MeV emission spectrum and was generally well described by a powerlaw spectral component with a photon index − 2. After the end of the keV−MeV prompt emission, this additional powerlaw component persists during hundreds of seconds, up to 19 h in the case of GRB 130427A (Ackermann et al 2014). Specifically, Ackermann et al (2013a) showed that the luminosity above 100 MeV decreases simply as L(t) ∝ t λ , with λ −1 at late times.…”
Section: Introductionmentioning
confidence: 99%
“…Our methodology is analogous to that of Ackermann et al (2014), who recently applied the DCF to cross-correlating the keV and MeV−GeV light curves of the bright Fermi-LAT-detected GRB 130427A. A similar approach was followed by Del Monte et al (2011).…”
Section: Introductionmentioning
confidence: 99%